Abordagens pedagógicas da educação física nas escolas públicas de Erechim, RS - Bagnara, Ivan Carlos (2012)
This study was developed within the line of Educational Processes and Language research. The investigation is focused on pedagogical approaches used for planning and development of physical education classes. We sought to identify the main approaches used to plan and conduct physical education classes in the final years of primary education in public schools in the urban area of Erechim / RS, in addition to research how the processes of continuing education influence in the implementation of physical education, relate the initial and continuing training with the pedagogical approaches used by physical education teachers and verify, in teacher s perception, if there is need for improvements in the educational development of the physical education teacher. With a quantitative and qualitative character, the research has used data produced by a questionnaire answered by fifty teachers and a semistructured interview with eight teachers selected from among those who participated in the first collection. To understand these data, we used the method of content analysis proposed by Navarro and Díaz (1994). The results suggest that physical education in Erechim s public schools still has a great influence of the traditional approach, considering that 38% of the teachers working in the final years of primary school exclusively use this approach for the development of classes. Added to the 28% who use at certain times of the year both the traditional approach such as renovating, this figure reaches 66%. Many teachers reported the preference for the traditional approach due to the security of working with it. Furthermore, regarding to the knowledge preferably used, 90% of the teachers prefer traditional sports, suggesting a sportivization exacerbated in the school environment. At this point, it is possible to identify that such sports are preferentially developed because of the student s taste and the physical space and materials targeted for this practice in the school environment. Regarding to continuing education, we found that 22% of teachers did not attended courses targeted for physical education with at least 20 hours in the last three years. The low demand for courses was justified by many of those interviewed by overspending and the little offer in the region. Finally, we are suggesting a new approach to be used by teachers to implement the physical education classes in the school context: the ethical-aesthetic approach, which has its epistemological foundations linked to aesthetic education, corporeality and the vast universe of physical culture movement. This approach is focused on the body, related to three lines: ethical and aesthetic aspects, which seeks to approach the pleasures of the body and its relationship to health; its social and cultural constitution and the concern with the standard image; the natural constitution of the body and its relationship with the corporeity, nature and technology